Hydroxypropyl methylcellulose and gum arabic composite edible coatings amended with geraniol to control postharvest brown rot and maintain quality of cold-stored plums - Asgarian, Z.S.; Palou, Lluís; Lima de Souza, Ricardo; Quintanilla, P.G.; Taberner, Verónica; Karimi, R; Perez-Gago, M.B. (2025)
In this study, the effect of hydroxypropyl methylcellulose (HPMC) and gum Arabic (GA) edible coatings amended with 0.2% geraniol (GE) were evaluated for the control of brown rot, caused by Monilinia fructicola, on artificially inoculated plums (Prunus salicina Lindl., cv. Angeleno) stored for 5 weeks at 1 °C. Brown rot is the most important pre- and postharvest fungal disease of stone fruits, causing severe economic losses worldwide. Geraniol is an important constituent of many essential oils that can be obtained as a byproduct from different industrial procedures, such as those of the juice industry. Fruit postharvest quality was also evaluated after 5 and 8 weeks of storage at 1 °C, followed by 3 days at 7 °C plus 5 days at 20 °C, simulating packinghouse, transport, and retail shelf-life conditions, respectively. HPMC coatings containing 0.2% GE reduced the incidence and severity of brown rot by 37.5 and 64.8%, respectively, compared to uncoated fruit after 5 weeks of storage at 1 °C. HPMC-coated plums, with and without GE, showed the highest level of firmness, the lowest change in external peel color parameters (L*, a*, b*, C*, hue), and the lowest flesh bleeding compared to uncoated control and GA-coated samples throughout the entire storage period, which correlated with a higher gas barrier of these coatings without negatively affecting sensory quality. Furthermore, the HPMC-0.2% GE coating provided the highest gloss to coated plums, showing the potential of this coating as a safe and environmentally friendly alternative to conventional fungicides and waxes for brown rot control and quality maintenance of coldstored plums